PS01.021: SHORT POEM GUIDED BY ENDOFLIP RESULTS IN LESS REFLUX RATE IN PATIENTS SUFFERING FROM ACHALASIA. (14th September 2018) - Barbieri, Lavinia; Ilczysyn, Andrei; Jafari, Jafar; Botha, Abraham; Smyth, Edel
Abstract: Background: Peroral Endoscopic Myotomy (POEM) has gained ground for achalasia tratment. Although laparoscopic Heller's-Dor (LHD) is a proven intervention, the cut of the inner muscular layer during POEM offers a goal-directed procedure. However, concerns regarding post-procedure reflux had been raised. As during POEM long myotomy is generally adviced, we decreased the length to reduce reflux after treatment. Methods: 19 patients with type 1 or 2 achalasia underwent POEM guided intraoperatively by Endoflip® (Crospon Ltd., Galway, Ireland) to target the myotomy where the major point of tightness was. We aimed for an increase of compliance and distensibility of three times of the lower esophageal sphincter (LOS) via a short myotomy. We compared these patients with a historic control LHD group of 15 patients in terms of Eckardt's score, GERD-HRQL questionnaire, high-resolution manometry to check pressure of the LOS 24h pH-impedence to measure acid exposure with minimum follow-up of 9 months. Results: Length of myotomy was 7 cm (6–10) for POEM and 9 cm for LHD. Median Eckard's score after POEM was 0.5 versus 2 for LHD group. Median Eckardt's score and GERD-HRQL were 0.5 vs 2 and 13 vs 15, respectively after POEM or LHD. 24h pH-monitoring revealed pathologic reflux in one patient after POEM and in 3 after LHD, with median acid % time of 0, 1 vs 1, 2. Data are summarized in table . Conclusion: POEM is effective in achieving symptom relief in patient with achalasia. Although randomized data are not available, reflux rate after POEM with short myotomy guided by Endoflip is comparable with LHD and lower than the data of literature. Disclosure: All authors have declared no conflicts of interest.